Alfalfa hay inclusion ratein wet corn gluten feed baseddiets - C.R. Mullins; K.N. Grigsby; Barry J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2008)
In this experiment, we evaluated the effects of varying alfalfa inclusion rate in diets containing 31% wet corn gluten feed on a dry matter basis. Eighty lactating Holstein cows were allocated into groups of 10 and assigned to 1 of 8 pens balanced for parity, stage of lactation, and milk yield. Diets were formulated to contain 0, 7, 14, or 21% alfalfa on a dry matter basis. Diets containing greater proportions of alfalfa had less corn silage and soybean meal but more corn grain. Feed intake, milk production, body weight, and body condition score were monitored, and effects of increasing alfalfa inclusion rate were assessed. As more alfalfa was included in the ration, cows consumed more feed and had a tendency to produce more solids- and energy-corrected milk. In contrast, body weight gain decreased in diets with more alfalfa. These changes in milk and body weight indicate that metabolizable energy utilization shifted from body weight gain to milk production when more alfalfa was fed. With this in mind, an economic model was constructed to determine whether the added production from including alfalfa is enough to justify incorporating it in this type of ration. The model demonstrated that, despite minor losses in productivity, decreasing alfalfa inclusion rate may improve farm profitability by reducing feed costs and expenses associated with manure handling.; Dairy Day, 2008, Kansas State University, Manhattan, KS, 2008; Dairy Research, 2008 is known as Dairy Day, 2008
Keywords: Dairy Day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-134-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1002; Dairy; Alfalfa hay; Wet corn gluten; Feed based diets; Inclusion rate